Herbivoria e fogo : seus efeitos em Chamaecrista neesiana (Mart. ex. Benth.) I. & B. (Caesalpinoidea) na vegetação do cerrado - Simão, Rivane Newmann (2005)
Herbivory, fact of animals feeding all, exudations, tissues or parts of plants, is pointed like one of the most important points in the vegetation structuralization and diversity. That can be influenced by some factors, the most importants are seasonality, spatial variation, environment and plant-herbivory-predator interactions. Native species from Cerrado are also influenced by fire. In response to herbivory attack, the plants have different defenses strategies, it can be chemical, physical and/or biotic. The aim of this study was analyze the impact of herbivory action in Chamaecrista neesiana (Caesalpinoidea), in pre and post natural burn periods, trying to understand the phenologic variation importance to the plant in response to herbivory and fire damage. The study was conducted in Clube Caça e Pesca Itororó de Uberlândia, Uberlândia-MG, in two stages. Firstly, pre-fire (June to September, 2004) and the second, post-fire (November, 2004 to February, 2005). The Burn occurred accidentally in the study reserve in October, 2004. For the study was marked 46 plants of Chamaecrista neesiana (Caesalpinoidea) shared in two groups: the Control one (n=21; without herbivorous insects removal) and the Treatment one (n=25; with herbivorous insects removal). On the plants with herbivorous removal was sprayed weekly a non-nitrogen and non-phophorus based insecticide. This kind of insecticide was used to do not have plants unnatural fertilization. The application of the insecticide occurs by covering the plants with a plastic during five minutes for, more than neighbor plants protection, increases the product effectiveness. The removal of herbivorous insects in Treatment Group occurs also by manual removal. The insects were also collected in non-marked plants, by the beating method and manual collection. The herbivory was measured monthly by visual measure, using a Grid for comparison by the virtual sharing, in eight parts, on the leaf of C. neesiana. Monthly was also observed the phenology dates, the vertical and lateral growing. On the young leafs was observed a lot of oil gland, to verify their function was get on 20 control pitfalls with water and detergent and others 20 was dirty on the edge of the pitfalls with this oil. The herbivory tax was smaller in the protected against herbivorous insects group than the non-protected one, and after the burn. We suggest that this fact occur because of the higher production of young leafs after burn, that happens because in the young leafs have the oil gland production, and we found that this oil gland works like a natural defense by insects, by the collection of more abundance in pitfalls without oil. On this way, was verified more susceptibility to foliar herbivory in mature stages. In C. neesiana, was not found compensatory effect of herbivory, because the vertical and lateral growing do not differ in the both groups (with and without herbivorous insect removal). The phenology showed the boom during the dry season (pre-fire), in the same period of the biggest diversity of insects, and in response to fire the flowering was anticipate in the years 2003 and 2005 (after burning) and occurred gradually, differently the year 2005 (before burning) that the flowering occurred in boom.